Effects of Musa sapientum (banana) and Ipomea batatas (sweet potato) extracts on the growth of Lactobacillus, E. Coli and S. Thyhimurium in monoculture and co-culture - Che Jaafar, Nor Zawani (2015)
Prebiotics are substrates that are able to promote the growth of beneficial bacteria in the intestine such as lactic acid bacteria. Commercial prebiotics are costly and to explore the possibility of obtaining prebiotic-like compound from local resources, the water and methanolic extracts of Musa sapientum (banana) and Ipomea batatas (sweet potato) peels were tested on the growth of beneficial bacteria. In this study, the growth of Lactobacillus reuteri C1, Lactobacillus salivarius I 24, Lactobacillus brevis I 25 and Lactobacillus gallinarum I 26 in the extracts were tested. The effects of the extracts on the growth of non beneficial bacteria such as Escherichia coli and Salmonella thyphimurium was also tested in mono and co- culture with Lactobacillus. The growth of the bacteria was compared against growth in the modified basal de Man Rogosa Sharpe (MRS) supplemented with 1% glucose for Lactobacillus and nutrient broth (NB) supplemented with 1% glucose for E. coli and S. thyphimurium. The results showed that the Lactobacillus have higher growth in the methanolic extracts. Lactobacillus reuteri C1 and L. gallinarum I26 achieved 8.48 log CFU/ml and 7.65 log CFU/ml, respectively after 24 hour incubation in methanolic extract of Musa sapientum. Lactobacillus sallivarius I24 achieved 7.68 log CFU/ml after 24 hour growth in methanolic extract of Ipomea batatas. Lactobacillus brevis I25 could grow equally well in methanolic extract of Musa sapientum and Ipomea batatas. Although the growth of E. coli and S. thyphimurium achieved 9.72 log CFU/ml and 10.00 log CFU/ml in Ipomea batatas water extraction and Ipomea batatas methanolic extraction, the growth of these bacteria was reduced when grown in co-culture with selected Lactobacillus strains. The growth of E. coli and S. thyphimurium was reduced by 3 to 5 log CFU/ml in water and methanolic extracts of Musa sapientum. Similarly the growth of E. coli and S. thyphimurium was reduced by 3 to 4 log CFU/ml in water and methanolic extracts of Ipomea batatas.